Microleakage of novel glass ionomer restoration in cavities prepared by Er,Cr:YSGG laser: An in-vitro study - Atas, Osman; Celenk, Sema; Aras, Ahmet (Wolters Kluwer Medknow Publications, 2020)
Aim: To compare the microleakage of novel materials containing glass ionomer, which are applied to standard class V cavities prepared by Er,Cr:YSGG (erbium, chromium-doped yttrium, scandium, gallium, and garnet) laser and by conventional diamond bur in primary teeth. Materials and Methods: Fifty non-carious primary molar teeth were randomly divided into five main groups and restored with various materials containing glass ionomers (Group 1: Equia System; Group 2: Fuji IX GP; Group 3: Fuji II LC; Group 4: Dyract Extra; and Group 5: Giomer). Each group was divided into two subgroups according to laser and conventional preparation methods. Results: As for the gingival margin, in terms of leakage values, no statistically significant difference was observed between drill and Er,Cr:YSGG laser although less microleakage values were obtained in Er,Cr:YSGG laser groups 1 and 4 (P > 0.05). Among groups prepared by drill, the lowest leakage rates observed at the gingival margin are Equia System, Giomer, Dyract Extra, Fuji II LC, and Fuji IX GP, respectively. Among groups prepared by Er,Cr:YSGG laser, the lowest leakage rates observed in the gingival edge are Equia System, Giomer = Dyract Extra, Fuji IX GP, and Fuji II LC, respectively. Conclusion: Occlusal and gingival microleakage scores were the lowest in the groups restored with Equia system in the cavities prepared by both diamond bur and laser system. Equia system consisting of high-viscosity glass ionomer cement and nano-filled surface coat G-Coat Plus materials could be used successfully in pediatric dentistry.
Keywords: Erbium; Chromium-Doped Yttrium; Scandium; Gallium; and Garnet Laser; Glass Ionomer; Microleakage; Restoration